«Las ignotas caras del amor» - Eduardo CHIRINOS (Caravelle)
This essay presents a new reading of the poem «El botánico» (Fábulas, 1971) written by the Argentinean Juan Gelman. The French scientist Aimé Bonpland’s fable which tries to transfer his system of signs to the Orinoco jungles and his meeting with Nunu the Indian woman, imagines the productive encounter between intertextuality, understood as the shifting of one sign system to another, and exile in its etymological sense of exsilire : «jump outwards».